Random walks and market efficiency: evidence from real estate investment trusts (REIT) subsectors - Almudhaf, Fahad; Hansz, Andrew J. (International Journal of Strategic Property Management, 2018)
This paper investigates the random walk behavior of real estate investment trust (REIT) subsectors using monthly return data from January 1994 to July 2015. Using variance ratio tests, we examine subsectors of lodging/resorts and self-storage and find that they do not follow a random walk, contradicting the weak-form efficient market hypothesis. Non-parametric runs tests help us find that office, industrial, mixed, free standing, shopping centers, apartments, manufactured homes, and timberland subsectors are weak-form efficient. The evidence in this study supports the idea that some subsec-tors are more informationally efficient than other subsectors.